Energy conservation for Malaysian Public Universities : a literature study / Nur Nadia Ismail, Alia Abdullah Salleh and Nur Azfahani Ahmad - Ismail, Nur Nadia; Abdullah Salleh, Alia; Ahmad, Nur Azfahani (2018)
Energy is commonly used widely around the world. This has led to a worrying scenario where more energy resources are extracted than found. Energy has become one of the essential inputs for social and economic development and a basic need in our modern life and contributes to a nation’s growth and development. The wastage of energy is a great concern for universities and other industry. Universities are a place of knowledge and it is justifiable to propose or applied this method. The objectives for this research was to propose the best method of energy conservation, in the field of non-structural energy conservation method, by using literature study. The variables that are established are awareness, stakeholder involvement, top management support and energy management team. This literature review was based on the five universities that were selected. This research will contribute towards knowledge in scope of energy conservation, as well to inspire universities to participate in energy conservation.